Perubahan Budaya Hukum dalam Eksekusi Jaminan Fidusia Berdasarkan Putusan MK No.18/PUU-XVII/2019 terhadap Debitur dan Kreditur - Mendrofa, Idaman Jaya; Sitorus, Saddan; Marselino, Meigel Rio; Sari, Elsi Karika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This examination aims to analyze the impact of changes in the legal culture regarding the execution of fiduciary security based on Constitutional Court Decision No. 18/PUU-XVII/2019. This decision brings significant reforms to the mechanism for executing fiduciary security by requiring the involvement of a court decision or the debtor a court decision before the execution process is carried out, ensuring a balance of legal protection between creditors and debtors. Prior to this decision, the execution of fiduciary security was commonly conducted unilaterally by the creditor, often leading to injustice for the debtor and creating an imbalance in the legal relationship between the partie. This examination employs a normative juridical approach to explore the impact of these legal provisions on the existing legal substance, culture and structure. The findings reveal a shift from a creditor-favorable approach to one that provides more equal protection for both parties, namely creditors and debtors. This change reflects efforts to enhance substantive justice in Indonesia's fiduciary system, emphasizing principles of fairness, transparency, and safeguarding the rights of all concerned parties. Furthermore, this study highlights the contribution of this decision in shaping a more adaptive and responsive legal system to meet the need for legal protection for all stakeholders in fiduciary transactions.